Therapeutic Effects of Medicinal Plants on Cutaneous Wound Healing in Humans: A Systematic Review - Tarcisio Vitor Augusto Lordani; Celia Eliane de Lara; Fabiana Borges Padilha Ferreira; Mariana de Souza Terron Monich; Claudinei Mesquita da Silva; Claudia Regina Felicetti Lordani; Fernanda Giacomini Bueno; Jorge Juarez Vieira Teixeira; Maria Valdrinez Campana Lonardoni (Mediators of Inflammation)
The pharmaceutical industry has made great strides in providing drugs that are able to stimulate the healing process, but only 1–3% of all drugs that are listed in Western pharmacopoeias are intended for use on the skin or cutaneous wounds. Of these, at least one-third are obtained from plants. We sought to review the therapeutic effects of medicinal plants on human skin lesions. For this systematic review, we searched the PubMed, Scopus, and Web of Science databases to identify clinical trials that were published from 1997 to 2017. We reviewed studies that described the use of medicinal plants for the treatment of skin lesions in humans. Ten studies were selected, eight of which were published from 2007 to 2016, with a total of 503 patients. Among the plant species that were used for the treatment of human skin lesions, 12 belonged to 11 families and were included in the analysis. All of the plant species that were studied presented high therapeutic potential for the treatment of cutaneous lesions.